Pax - Pennypacker, Sara, 1951-; Klassen, Jon (İstanbul : Epsilon, 2020)
"After being forced to give up his pet fox Pax, a young boy named Peter decides to leave home and get his best friend back"--Provided by publisher.
Booklist starred
Pub Weekly
School Library Journal starred
Booklist starred, November 2015
Kirkus Starred, November 2015
Pub Weekly, November 2015
Keywords: Foxes as pets -- Juvenile fiction; Human-animal relationships -- Juvenile fiction; Foxes as pets -- Fiction; Human-animal relationships -- Fiction; Foxes as pets -- Fiction; Human-animal relationship -- Fiction